Guide to the birds of China - MacKinnon, John (Oxford University Press, 2022)
"China covers about 7% of the earth's land surface and encompasses a hugely diverse range of habitats. As a result, it boasts a rich and diverse avifauna, including some of the most spectacular and fascinating birds to be found anywhere in the world. Building on the enormous popularity and reputation of the original A Field Guide to the Birds of China (2000), John MacKinnon's fully updated and refreshed work remains a truly comprehensive, taxonomically modern, fully illustrated, and authoritative field guide. 1474 bird species are richly illustrated in 164 annotated colour plates, which are closely integrated with up-to-date colour distribution maps, QR codes providing easy access to birdcalls, IUCN Red List status indicators and new, concise descriptions. These descriptions feature key observations as well as conveying crucial changes to species distributions resulting from climate change and landscape transformation. Guide to the Birds of China will appeal to an international and growing audience of professional and amateur ornithologists and birding enthusiasts, academic researchers and students, wildlife photographers, and conservationists"--Provided by publisher.